Serum Levels of Advanced Oxidation Protein Products and some Liver Function Markers in Chronic Myeloid Leukemia-Chronic Phase Patients Receiving Imatinib or Nilotinib - Khammas, Ikhlas; Ali Abdulhussain Kasim; Bassam Francis (Iraqi Journal of Pharmaceutical Sciences, 2025)
The treatment of chronic myeloid leukemia has witnessed substantial advancements by the introduction of tyrosine kinase inhibitors. Oxidative stress has been proposed as potential mechanism for resistance to their action. Simultaneously, oxidative stress has a crucial role in hepatic diseases and hepatocytes damage. The study aims to investigate the serum levels and potential correlation of the advanced oxidation protein products (AOPPs), as indicator of oxidative stress, with some markers of liver function. A total of 76 chronic myeloid leukemia-chronic phase patients were enrolled in this transverse, single center study. The enrolled patients were grouped as these receiving imatinib, at an oral dose of 400 mg/ day, and these who failed to clinically respond to imatinib and were switched to nilotinib, at an oral dose of 800 mg/ day. Serum levels of the advanced oxidation products (AOPPs), the hepatic enzymes alkaline phosphatase (ALP), alanine aminotransferase (ALT), aspartate aminotransferase (AST), and total serum bilirubin (TSB) as well as direct and indirect bilirubin were measured. The enrolled patients in both groups were of comparable age and gender; P˃0.05. Serum ALT level was higher, and serum AOPPs, total and direct bilirubin levels were lower in patients receiving imatinib compared to these receiving nilotinib; there was no significant correlation between the serum levels of AOPPs and that of liver function markers whether in the pooled data of total participants or based on the type of medication used. In conclusion, the oxidative stress, indicated by AOPPs, and bilirubin metabolism is significantly deranged in chronic myeloid leukemia-chronic phase patients receiving nilotinib as compared to these receiving imatinib.